Acapulco and Costa Chica, colonial buildings of cultural diversity. Reflections from register of 1777 - Quiroz Malca, Haydée (2017)
Acapulco and the region known as the Costa Chica of Guerrero, are some of the first places that we record on cultural diversity of human groups who settled there from the pre-Hispanic era. This phenomenon is accentuated with the arrival of the conquerors time when they make their appearance and authentic Spanish and mestizos, and the African people or their descendants, who were referred to as mulattoes and blacks lovos. In this article, we propose some analytical comments pointing the diverse composition of this region, taking as initial starting point a census of the population of Acapulco, it made the eighteenth century, in which the groups that lived at that time are recorded, including the dominators (Spaniards and mestizos), to-population and called Indians- origen poblation –and called Chinese, it was the meaning that was given to those who came basically from the Philippines. Emphasize that the majority population (above 60%) was the black African origin and their mixtures called, mulattos and lovos. From the data of this source, I will project some working hypotheses to better understand the current composition and construction of the town of Acapulco and Costa Chica, he had a clear colonial origin.